Home Healthcare Nurses' Attitudes, Confidence, and Engagement in Evidence-Based Practice. (March 2019) - Thiel, Linda M.; Ko, Arthur; Turner, Jill A.
Abstract : Evidence-based practice (EBP) is becoming standard in today's healthcare arena and home care organizations are not exempt from integrating evidence into practice to improve patient outcomes. There is a scarcity of research literature that examines the behaviors and attitudes of home healthcare nurses (HHNs) regarding EBP. In this study, a descriptive survey design was used to investigate HHNs' a) information-seeking behaviors when providing nursing care, b) administrative support for EBP (as perceived by HHNs), c) attitudes toward EBP, and d) EBP engagement and confidence in providing EBP nursing care. Self-reported data were collected by internet and paper survey. The survey consisted of a 65-item questionnaire that included the Nurses' Attitudes Toward Evidence-Based Practice Scale, which has previously established validity and reliability. A convenience sample of 95 HHNs participated in the study. Results suggest HHNs' EBP attitudes are positive. A positive and significant relationship was found between attitudes and hours worked ( r = 0.21, p = 0.047) and educational level ( r = 0.45, p = 0.0001); 95% confidence level. Confidence levels in providing EBP care were moderate, and HHNs did not perceive EBP as an agency priority. HHNs need to be supported and encouraged in the facilitation of EBP, a task made easier when they are knowledgeable about EBP, have confidence in their EBP skills, and have the support of their organizations.